Fetal Cardiac Timing Events Estimation From Doppler Ultrasound Signals Using Swarm Decomposition - Alnuaimi, Saeed; Jimaa, Shihab; Kimura, Yoshitaka; Apostolidis, Georgios K.; Hadjileontiadis, Leontios J.; Khandoker, Ahsan H. (Frontiers in Physiology, 2019)
Perinatal morbidity and mortality can be reduced when any cardiac abnormalities during a pregnancy are diagnosed early. Doppler ultrasound signals (DUS) are often used to monitor the heart rate of a fetus and they can also be used to identify the timing events of fetal cardiac valve motions. This paper proposed a novel, noninvasive technique which can be used to identify the fetal cardiac timing events based upon the analysis of fetal DUS (based upon 66 normal subjects belonging to three differing age groups) which can later be used to estimate fetal cardiac intervals from a DUS signal. The foundation of this method is a novel decomposition method referred to as Swarm Decomposition (SWD) which makes it possible for the frequency contents of Doppler signals to be associated with cardiac valve motions. These motions include the opening (o) and closing (c) of Aortic (A) and Mitral (M) valves. When compared to the empirical mode decomposition (EMD), SWD results achieve a higher accuracy when isolating the constituent parts of analyzed DUS signals. Pulsed Doppler images are used in order to verify the estimated timings. Three fetal age groups were assessed in terms of their cardiac intervals: 16-29, 30-35, and 36-41 weeks. The proposed method was used to estimate the following fetal cardiac intervals: Systolic Time Interval (STI), Isovolumic Relaxation Time (IRT), Pre-ejection Period (PEP), and Ventricular Ejection Time (VET). The evaluation of fetal cardiac performance can be enhanced, given that these findings can be leveraged as sensitive markers throughout the process.